Luminescent solar concentrators: challenges for lanthanide-based organic-inorganic hybrid materials - Correia, Sandra F. H.
Luminescent solar concentrators (LSCs) are devices comprising a transparent matrix embedding optically active centres that absorb the incident radiation, which is re-emitted at a specific wavelength and transferred by total internal reflection to photovoltaic (PV) cells located at the edges of the matrix. Organic-inorganic hybrids incarcerating trivalent lanthanide ions (Ln(3+)) are a very promising class of materials for addressing the required challenges in the LSC design to improve solar energy harvesting and, then, PV energy conversion. This feature article offers a general overview of the potential of down-shifting-based Ln(3+)-containing organic-inorganic hybrids for the development of the area with special focus on (i) optically active layer design, (ii) energy conversion mechanisms, (iii) performance and geometry and (iv) figures of merit in PV cell enhancement. Finally, a prospective outlook on future progress, e.g. optically active centre alignment, geometry optimization and building integration, is provided. The use of Ln(3+)-containing hybrids in LSCs is at an infant initial research step and considerable basic knowledge is still needed to enable prototypes to become a commercial reality.